Significant Factors to Motivate Small and Medium Enterprise (SME) Construction Firms in the Philippines to Implement ISO9001:2008. (2017) - Juanzon, Joseph Berlin P.; Muhi, Manuel M.
Abstract: Motivating SME-based construction firms to adopt different management systems is not a simple task, especially if they are not aware of the benefits that they will gain from the new process-based management system. The implementation of ISO 9001:2008 Quality Management System in the construction industry is an ongoing trend, more so in the Small and Medium Enterprise. However, the level of awareness and readiness of the construction industry in the Philippines is still low as compared to the neighboring countries in Asia and in the western countries where ISO 9001:2008 originated. The purpose of this research is to determine the significant factors that will motivate SME-based construction firms in the Philippines to implement ISO 9001:2008. A field study was conducted on SME based construction firms in the Philippines, wherein a total of 139 respondents out of the 613 SME-based construction firms in CALABARZON areas were surveyed. Results reveal that the three main factors that will motivate SME-based construction firms to implement ISO 9001:2008 are (1) if required by their clients, (2) to qualify for bidding and (3) to increase customer satisfaction. Therefore, based on the results and findings, a certification of ISO 9001:2008 from an accredited auditor shall be required by clients as a constituent in accrediting SME-based construction firms and to qualify for bidding.